Cognitive neuroscience of metacognition - Friedemann, M; Bang, D; Yeung, N (Sage Publishing, 2023)
This chapter explores the neural underpinnings of metacognition – the monitoring and controlling of one’s own thoughts. After first defining metacognition and describing how it can be measured, we discuss the evidence for explicit representations of metacognitive signals, reviewing neuroimaging studies that have dissociated metacognitive from object-level processes. Further, we consider the functional value of metacognition, including the social sharing of confidence estimates for group decision-making. Finally, we review research debates that cognitive neuroscience research may help address, focusing on how metacognition is represented in the brain, the relationship between metacognition and Theory of Mind, and the nature of metacognitive deficits in psychiatric disorders.